Analisis Tingkat Kesehatan Bank Umum Syariah Menggunakan Metode Rgec - Deva Arly Khusuma; Isro’iyatul Mubarokah (Peneliti.net, 2023)
A bank when carrying out its roles and functions should be in a healthy condition, meaning that when a bank is not in a healthy condition it will have an adverse impact on the performance of the bank's management and can be dangerous for other parties such as customers who have entrusted their funds to be managed. The level of soundness or bad performance of a bank is assessed by several indicators, Bank Indonesia (BI) uses the RBBR method as a substitute for the previous method which is deemed less effective. Thus the author's goal is to be able to assess the soundness level of an Islamic Commercial Bank (BUS) which is found on the official website http://www.ojk.go.id using the Risk Based Bank Rating (RBBR) method for the 2017 period to the 2021 period. The results obtained are in the form of criteria for whether or not a bank is healthy based on a predetermined predicate.